O uso do marketing B2B em pequenas e médias empresas: um estudo exploratório no setor de automação industrial do Vale do Paraíba paulista - Garcia, Adriana Bernadete Barros Carvalho [UNESP] (2014)
This study aimed to analyze the use of B2B marketing in small and medium enterprises in the industrial automation industry. Its motivation derives from the relevance of generating knowledge on how to improve the use of marketing strategies and tools in small businesses. The literature review allowed to define a set of four major areas of decision-making on the use of B2B marketing, namely: target market, positioning, marketing strategy and customer relationships. Each of these areas was analysed through different aspects. Data collection was conducted through semi-structured interviews with representatives of companies. The interviews were pre-tested. In accordance with the exploratory nature of the research and the qualitative approach, a purposive sample of companies representative of the sector in the region was defined. Analysis was made for each individual company and for the whole sample set. The results indicate that leaders do not define their market through planning and information collection. Companies do not base their quest for competitiveness in positioning and value creation tools, nor try to identify the level of quality and image perceived by their clients. In general, the use of strategies and marketing tools is still incipient, although the leaders maintain just nominally their importance